Feasibility of Al-Muthalaah Teaching Materials Based on Miles and Huberman Model Analysis and Pancasila Student Profile - Anisa; Asep Sopian; Hanip Hidayatulloh (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
Arabic plays an important role in the history of education in Indonesia and must remain as focus of attention. Arabic language learning at MTs under the Ministry of Religious Affairs needs to be well-integrated into the existing curriculum, so that it is relevant to the values promoted by the current vision of Indonesian Education, especially the Pancasila Student Profile which focuses on building the character of students. However, in practice, Arabic language teaching materials at MTs are not fully connected to these values.  For this reason, efforts are needed to test the feasibility of one of the teaching materials. In this context, the researcher chose the teaching material "al-Muthalaah" by Abu Abdurrohman to test its feasibility for the Pancasila Student Profile. Exploratory descriptives will be used in this feasibility test with the Miles and Huberman model data analysis technique. The validation test was carried out by two experts, including a material expert and a media expert. The validation test results show that al-Muthalaah's teaching materials received an average score of 87.75% and were categorized as extremely valid by material experts. The aspect of the relevance of teaching materials to the Pancasila Student Profile also received a high score with 95%. However, media experts gave an average score of 80% with the category being sufficiently valid and requiring slight revision. This shows that Al-Muthala'ah teaching materials were declared feasible and relevant to be applied in Arabic language learning at MTs. So that it can become practical material for aligning ourselves with the vision promoted by the government and also helps students understand and internalize the values that support their interactions with the surrounding environment.